The Impact of Knowledge about the Environment on the Attitudes and Behavior of Young Consumers in the Food Market - Fairuz, Hilmia Safa; Ageng, Nanda Kurnia; Kurniaty, Dewi (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study examines the impact of environmental knowledge on the attitudes and behaviors of young consumers in the food market. This study found that consumers are increasingly recognizing the importance of green products and manufacturers are responding by incorporating green aspects into their marketing strategies. This study also found that there is a positive correlation between environmental knowledge and consumer attitudes and behaviors. This study used quantitative methods and analysed the data using regression analysis. The result show that both consumer attitudes and behaviors have a significant impact on environmental knowledge.